2003
DOI: 10.1051/0004-6361:20021676
|View full text |Cite
|
Sign up to set email alerts
|

A search for period changes inδScuti stars with the super-LOTIS sky patrol system

Abstract: Abstract.We have observed a sample of δ Scuti stars discovered by the ROTSE collaboration in 1999 with Super-LOTIS in order to characterize changes in their pulsation periods over a time baseline of roughly three years. Achieving these goals required the creation of an automated astrometric and photometric data reduction pipeline for the Super-LOTIS camera. Applying this pipeline to data from a June 2002 observing campaign, we detect pulsations in 18 objects, and find that in two cases the periods have changed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Our results suggest that resonant three-mode interactions can be significant in δ Sct stars, and the ubiquity of large μ across all of our models may explain why amplitude variations (Bowman et al 2016) and large P P  (Breger & Pamyatnykh 1998;Blake et al 2003;Bowman et al 2021) are commonly observed. However, our analysis did not model the parent driving and therefore did not solve for the overall mode amplitudes, nor for their relation to the surface flux perturbations.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our results suggest that resonant three-mode interactions can be significant in δ Sct stars, and the ubiquity of large μ across all of our models may explain why amplitude variations (Bowman et al 2016) and large P P  (Breger & Pamyatnykh 1998;Blake et al 2003;Bowman et al 2021) are commonly observed. However, our analysis did not model the parent driving and therefore did not solve for the overall mode amplitudes, nor for their relation to the surface flux perturbations.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Bowman et al (2021) find that the fundamental and first-overtone radial modes of the HADS star KIC 5950759 exhibits a linear period change P P 10 yr 6 1   -over a timescale of several years, at least two orders of magnitude higher than predicted by evolutionary models. Both Breger & Pamyatnykh (1998) and Bowman et al (2021) suggest (see also Blake et al 2003) that the rapid period changes could be the result of nonlinear mode interactions. These interactions can enable a fast transfer of energy among the modes and induce rapid amplitude-dependent variations in their oscillation periods.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that the classifying methods of survey data should be more precise by adding more criteria, specifically to discriminate between the HADS and W UMa stars. Blake et al (2003) studied the period changes of 18 ROTSE-I δ Scuti stars by comparing their result with ROTSE-I data. Four of their objects are the same with this study.…”
Section: Discussionmentioning
confidence: 99%
“…From 1999 to 2003 Super-LOTIS was configured with a prime focus imager in order to provide better coverage of the large Burst and Transient Source Experiment (BATSE) error boxes. Selected results from that system and its predecessor, LOTIS, are included in Park et al [2], Williams et al [3], Schaefer et al [4], Park et al [5], Hurley et al [6], Castro Cerón et al [7], and Blake et al [8].…”
Section: System Overviewmentioning
confidence: 99%